2020
DOI: 10.1039/d0cy01577f
|View full text |Cite
|
Sign up to set email alerts
|

P-doped nickel sulfide nanosheet arrays for alkaline overall water splitting

Abstract: Heazlewoodite, Ni3S2, is one of the most promising bifunctional electrocatalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline media due to its metallic conductivity and low...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Like in metal oxides and hydroxides, Fe doping is evident in significantly improving the OER activity of TM sulfides. 139,140 147 257 mV @ 50 mA cm -2 81 24 h @ 0.6 V vs Ag/AgCl 1 M KOH Co-doped WS2 148 303 mV @ 10 mA cm -2 79 -1 M KOH CoFeS/CNT-P 1000 149 309 mV @ 100 mA cm -2 47 12 h @ 20 mA cm -2 1 M KOH Fe-doped CoS 141 290 mV @ 10 mA cm -2 52.6 10 h @ 10 mA cm -2 1 M KOH Fe-doped Co9S8 142 270 mV @ 10 mA cm -2 70 10 h @ 270 mV 1 M KOH Fe-doped NiS2 143 231 mV @ 100 mA cm -2 43 15 h @ 20 mA cm -2 1 M KOH Fe-doped Ni3S2 144 223 mV @ 200 mA cm -2 55.7 14 h @ 223 mV 1 M KOH Fe-doped Ni3S2/NF 139 249 mV @ 100 mA cm -2 42 20 h @ 270 mV 1 M KOH Fe2.1% doped Ni3S2/NF 140 213 mV @ 100 mA cm -2 33.2 -1 M KOH Fe-doped H-CoMoS 145 282 mV @ 10 mA cm -2 58 1 M KOH Ni1.29Co1.49Mn0.22S4 150 348 mV @ 10 mA cm -2 65 40,000 s @ 10 mA cm -2 1 M KOH N-doped Co9S8/G 151 409 mV @ 10 mA cm -2 82.7 -0.1 M KOH Ni-doped FeS 152 228 mV @ 10 mA cm -2 53 10 h @ 1.47 V vs RHE 1 M KOH N2-NiS2-500 153 270 mV @ 10 mA cm -2 40 h @ 270 mV 1 M KOH (N-Ni3S2@C)/NF 154 310 mV @ 100 mA cm -2 75 20 h @ 1.70 V vs RHE 1 M KOH N-doped NiS/NiS2 155 270 mV @ 10 mA cm -2 99 20 h @ 270 mV 1 M KOH P-doped Co-Ni-S Nanosheets 156 296 mV @ 100 mA cm -2 61.1 16 h @ 10 mA cm -2 1 M KOH P-Ni3S2/NF 157 256 mV @ 10 mA cm -2 30 30 h @ 1.525 V vs RHE 1 M KOH P-Ni3S2/NF 158 306 mV @ 100 mA cm -2 99 10 h @ 1.54 V vs RHE 1 M KOH (P-(Ni,Fe)3S2/NF 159 196 mV @ 10 mA cm -2 30 15 h @ 295 mV 1 M KOH Zn-doped Ni3S2 160 330 mV @ 100 mA cm -2 87 20 h @ 300 mV 1 M KOH Metal selenides Fe-doped CoSe2/NF 161 256 mV @ 100 mA cm -2 35.6 10 h @ 231 mV 1 M KOH Ag-doped CoSe2 nanobelts 162 320 mV @ 10 mA cm -2 56 -0.1 M KOH B-doped Fe5Co4Ni20Se36 163 279.8 mV @ 10 mA cm -2 59.5 10 h @ 10 mA cm -2 1 M KOH Co-doped NiSe 164 380 mV @ 100 mA cm -2 111 >10 h @ 320mV 1 M KOH Co-doped Nickel selenide 165 275 mV @ 30 mA cm -2 63 24 h @ 1.5 V vs RHE 1 M KOH Co0.75Fe0.25(S0.2Se0.8)2 166 293 mV @ 10 mA cm -2 77 -1 M KOH Cu-14-Co3Se4/GC…”
Section: Metal Sulfidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Like in metal oxides and hydroxides, Fe doping is evident in significantly improving the OER activity of TM sulfides. 139,140 147 257 mV @ 50 mA cm -2 81 24 h @ 0.6 V vs Ag/AgCl 1 M KOH Co-doped WS2 148 303 mV @ 10 mA cm -2 79 -1 M KOH CoFeS/CNT-P 1000 149 309 mV @ 100 mA cm -2 47 12 h @ 20 mA cm -2 1 M KOH Fe-doped CoS 141 290 mV @ 10 mA cm -2 52.6 10 h @ 10 mA cm -2 1 M KOH Fe-doped Co9S8 142 270 mV @ 10 mA cm -2 70 10 h @ 270 mV 1 M KOH Fe-doped NiS2 143 231 mV @ 100 mA cm -2 43 15 h @ 20 mA cm -2 1 M KOH Fe-doped Ni3S2 144 223 mV @ 200 mA cm -2 55.7 14 h @ 223 mV 1 M KOH Fe-doped Ni3S2/NF 139 249 mV @ 100 mA cm -2 42 20 h @ 270 mV 1 M KOH Fe2.1% doped Ni3S2/NF 140 213 mV @ 100 mA cm -2 33.2 -1 M KOH Fe-doped H-CoMoS 145 282 mV @ 10 mA cm -2 58 1 M KOH Ni1.29Co1.49Mn0.22S4 150 348 mV @ 10 mA cm -2 65 40,000 s @ 10 mA cm -2 1 M KOH N-doped Co9S8/G 151 409 mV @ 10 mA cm -2 82.7 -0.1 M KOH Ni-doped FeS 152 228 mV @ 10 mA cm -2 53 10 h @ 1.47 V vs RHE 1 M KOH N2-NiS2-500 153 270 mV @ 10 mA cm -2 40 h @ 270 mV 1 M KOH (N-Ni3S2@C)/NF 154 310 mV @ 100 mA cm -2 75 20 h @ 1.70 V vs RHE 1 M KOH N-doped NiS/NiS2 155 270 mV @ 10 mA cm -2 99 20 h @ 270 mV 1 M KOH P-doped Co-Ni-S Nanosheets 156 296 mV @ 100 mA cm -2 61.1 16 h @ 10 mA cm -2 1 M KOH P-Ni3S2/NF 157 256 mV @ 10 mA cm -2 30 30 h @ 1.525 V vs RHE 1 M KOH P-Ni3S2/NF 158 306 mV @ 100 mA cm -2 99 10 h @ 1.54 V vs RHE 1 M KOH (P-(Ni,Fe)3S2/NF 159 196 mV @ 10 mA cm -2 30 15 h @ 295 mV 1 M KOH Zn-doped Ni3S2 160 330 mV @ 100 mA cm -2 87 20 h @ 300 mV 1 M KOH Metal selenides Fe-doped CoSe2/NF 161 256 mV @ 100 mA cm -2 35.6 10 h @ 231 mV 1 M KOH Ag-doped CoSe2 nanobelts 162 320 mV @ 10 mA cm -2 56 -0.1 M KOH B-doped Fe5Co4Ni20Se36 163 279.8 mV @ 10 mA cm -2 59.5 10 h @ 10 mA cm -2 1 M KOH Co-doped NiSe 164 380 mV @ 100 mA cm -2 111 >10 h @ 320mV 1 M KOH Co-doped Nickel selenide 165 275 mV @ 30 mA cm -2 63 24 h @ 1.5 V vs RHE 1 M KOH Co0.75Fe0.25(S0.2Se0.8)2 166 293 mV @ 10 mA cm -2 77 -1 M KOH Cu-14-Co3Se4/GC…”
Section: Metal Sulfidesmentioning
confidence: 99%
“…Recently, researchers reported incorporating non-metals, such as N, P, and F, into the lattice of metal sulfides to improve their electrocatalytic capability. 149,151,[153][154][155][156][157][158][159]180 superior durability for 20 h at 1.7 V with ~93% retention of its initial activity. 154 The experimental results indicate that N doping plays a key role in the quick discharging of OER intermediates and improved intrinsic activity.…”
Section: Journal Of Materials Chemistry a Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid economic development and population growth have caused massive consumption of fossil fuels, global warming, and severe environmental issues. Consequently, searching for sustainable and efficient clean energy is crucial. Hydrogen (H 2 ) energy has become an important replacement to traditional fossil resources for its high energy density and clean and zero pollution. Electrochemical water splitting is currently considered as a reliable pathway to produce hydrogen attributed to its unique carbon-free emission and storage advantages. However, Pt-based catalysts used for accelerating the hydrogen evolution reaction (HER) at the cathode are expensive and scarce resources on earth. Therefore, earth-rich, highly efficient catalysts such as nonnoble metals or compounds are urgently required to improve the energy conversion efficiency from electric to chemical energy.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, cation/anion doping has been successfully proved to modulate the electronic structure of electrocatalysts by changing the coordinated environment of the metal center. , Compared with cation doping, anion doping offers many other benefits in addition to tuning the electronic structure, such as avoiding the confusion of active sites and saving cost . Various anions including N, P, and F have been proven to efficiently promote the electrocatalytic performance of Ni 3 S 2 for HER. For example, our group has demonstrated that the introduction of substantial fluorine anions into the Ni 3 S 2 catalyst could obviously enhance its HER catalytic performance and revealed that the strong electronegativity of F anions is beneficial for enhancing the intrinsic activity.…”
Section: Introductionmentioning
confidence: 99%